Monitoring of distributed Java applications - Bubak, Marian; Funika, Włodzimierz; Wismüller, Roland; Mętel, Piotr; Orłowski, Rafał (Future generation computer systems, 2003)
The paper presents an approach to distributed Java monitoring based on an extension to the on-line monitoring interface specification that defines relationships between a monitoring system and on-line tools used to support the development of Java applications. The extension aims at defining a standard for an open interface that supports on-line software development tools. The paper also presents the implementation ideas on building a monitoring infrastructure based on the specification. This comprises the architecture of the infrastructure, the mechanism of interaction with the Java virtual machine, and sample scenarios of interactions between the tool and the monitoring system. The infrastructure provides a uniform monitoring support for different kinds of tools, like debuggers or performance analysers.